2020
DOI: 10.1111/jgh.15358
|View full text |Cite
|
Sign up to set email alerts
|

FibroScan–aspartate aminotransferase score in an Asian cohort of non‐alcoholic fatty liver disease and its utility in predicting histological resolution with bariatric surgery

Abstract: Background and Aim The FibroScan–aspartate aminotransferase (FAST) score was developed for identifying patients with non‐alcoholic steatohepatitis, who also have an elevated non‐alcoholic fatty liver disease (NAFLD) activity score (NAS) ≥ 4 and significant fibrosis (F ≥ 2). We aimed to validate it in our NAFLD cohort and assess if it correlates with the histological changes after bariatric surgery. Methods Patients with NAFLD, including those undergoing bariatric surgery, were included. The FAST score was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Our findings are further corroborated by a recent study, reporting an AUROC of 0.79 with the FAST score for detecting NASH + NAS $4 + F $ 2 in Indian patients with NAFLD. 33 Using the cut-offs proposed by Newsome et al 6 in our cohort, we found that the rule-out cut-off (FAST: #0.35) had an NPV of 0.88 with a negative LR of 0.64. 6 However, the rule-in cut-off (FAST: $0.67) had a PPV of only 0.33 with a positive LR of 2.23.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Our findings are further corroborated by a recent study, reporting an AUROC of 0.79 with the FAST score for detecting NASH + NAS $4 + F $ 2 in Indian patients with NAFLD. 33 Using the cut-offs proposed by Newsome et al 6 in our cohort, we found that the rule-out cut-off (FAST: #0.35) had an NPV of 0.88 with a negative LR of 0.64. 6 However, the rule-in cut-off (FAST: $0.67) had a PPV of only 0.33 with a positive LR of 2.23.…”
Section: Discussionmentioning
confidence: 49%
“…The PPVs of the rule-in cut-off (FAST: $0.67) in these 3 cohorts were 0.33, 0.63 and 0.54, respectively. 6 Similarly, Anand et al 33 recently reported poor PPV (0.43) and positive LR (2.53) with these cut-offs in their cohort of Indian patients with NAFLD where the proportion of NASH + NAS $ 4 + F $ 2 was 23%.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, because weight loss after bariatric surgery may induce a significant improvement of NAFLD metabolic profile and liver histopathology, 26 there is a growing need of non‐invasive biomarkers to assess the liver response to therapeutic interventions, including bariatric surgery. It is thus important to assess whether this P. copri dominant microbiome cluster, alone or in combination with other non‐invasive diagnostic methods, 27 may be used as a biomarker to assess metabolic and histological improvement in NASH patients after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These are fairly similar to the reductions seen at 72 weeks in a recent double-blind phase 2 trial in patients with biopsy-confirmed NASH for the highest daily dose of 0.4 mg semaglutide used there, namely − 39 dB/m, 0.52, 0.42, and 0.72, respectively [3]. In bariatric surgery, studies with a varying proportion of gastric bypass found that CAP was reduced by 62 to 75 dB/m and mean or median LSM by a factor of 0.7 to 0.8 [32][33][34][35]. However, a direct comparison of bariatric surgery, DJBL, and GLP-1 agonists has not yet been conducted and merits a prospective trial with special attention to modulation of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%